The Effect of Problem Based Learning Model on Creative and Critical Thinking Skills in Static Fluid Topics - Wenno, Izaak Hendrik; Jamaludin, Jamaludin; Batlolona*, John Rafafy (Universitas Syiah Kuala, 2021)
Creative and critical thinking skills are one of the demands of new skills needed by students in the current era. One of the learning models that can sharpen creative and critical thinking skills is Problem based learning (PBL). Heretofore, research related to creative and critical thinking skills with PBL in understanding static fluid material is still minimal. Therefore, this research explored it. This study aimed to analyze the effect of PBL on students' creative and critical thinking skills. This type of research is experimental with a total of 58 students, both experimental class and control class in 10th-grade science class Christian Senior High School YPKPM Ambon. The research procedure in the form of creative and critical thinking skills tests carried out during the research process and data analysis used was the independent sample t-test. The results showed that the average value of the experimental class students' learning achievement related to students' creative and critical thinking skills was higher than the conventional class. This implies that PBL facilitates in improving students' creative and critical thinking skills on static fluid.